Health Seeking Behaviour Among Adult Orang Asli (Indigenous Peoples) From Rural Negeri Sembilan, Malaysia: A Mixed-methods Study. - Muslimah Ithnin; Nadia Mohd Effendy; Mohd Dzulkhairi Bin Mohd Rani; Nadeeya'ayn Umaisara Mohamad Nor; Norsham Juliana Nordin (Malaysian Public Health Physicians’ Association, 2024)
Indexed by MyCite